Didactic engineering supporting the use of gamification applied to the teaching of arithmetic operations - Santiago, Paulo Vitor da Silva; Alves, Francisco Régis Vieira (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background:This study proposes an instructional method aimed at resolving arithmetic problems in mathematics. It is specifically tailored to assist educators in their initial mathematical training and to enhance classroom mathematics teaching through the implementation of Gamification.Aim:The objective of this research is to explore the contributions of didactic engineering and digital technologies, particularly those incorporating gamification, in full-time secondary school education, with an emphasis on basic arithmetic operations.Method:The methodology employed in this study is based on and structured around Didactic Engineering research techniques. It is an exploratory, qualitative research designed to simplify the understanding of mathematical problems through the use of Digital Technologies.Results:The findings of this research are categorized into stages: preliminary analysis, a priori analysis, experimentation, and a posteriori analysis and validation. It was observed that the application of problems in the classroom validated the strategies employed.Conclusion:The results indicate that the implemented gamified activities positively influenced teachers’ perspectives on how these activities, particularly the two games designed in Google Presentations, support the teaching and learning processes in mathematics for students.